Quantification of brain-derived extracellular vesicles in plasma as a biomarker to diagnose Parkinson's and related diseases. (April 2019) - Ohmichi, Takuma; Mitsuhashi, Masato; Tatebe, Harutsugu; Kasai, Takashi; Ali El-Agnaf, Omar M.; Tokuda, Takahiko
Abstract: Introduction: There is still a substantial unmet need for blood-based biomarkers to make an objective diagnosis of Parkinson's disease (PD) and the parkinsonism-plus syndromes. This study is aimed to determine whether enumeration of brain-derived exosomes (BDEs) in plasma is informative in the diagnosis of those diseases. Methods: We have developed a specific method to enumerate the plasma levels of neuron-derived, astrocyte-derived, and oligodendrocyte-derived exosomes (NDEs, ADEs and ODEs, respectively), and quantified them individually in patients with PD (n = 15), multiple system atrophy (MSA, n = 15), progressive supranuclear palsy (PSP, n = 7) and disease controls (n = 15). Our assays employ specific antibodies against molecules expressed by neurons, astrocytes and oligodendrocytes, respectively, combined with an antibody to the exosome common marker CD81. Results: The plasma levels of NDEs showed significant increase in PD compared to control (p < 0.01) and MSA (p < 0.05) (one-way ANOVA, Bonferroni post hoc test). The plasma levels of ODEs and the ratio of ODE/NDE showed a significant correlation with UPDRS part III scores in the patients with MSA with predominant parkinsonism (MSA-P) (r 2  = 0.57, n = 6, p = 0.048) and in the patients with PD (r 2  = 0.51, n = 14, p = 0.0041), respectively. Conclusions: This is the first paper that enumerated NDE, ADE, and ODE in human plasma and showed the usefulness of those levels as biomarkers for PD. Our results suggest the capability of the plasma levels of NDE and ODE as a diagnostic and surrogate biomarker for PD and MSA-P, respectively. Highlights: Neuron-, astrocyte-, and oligodendrocyte-derived exosomes (NDEs, ADEs, ODEs) in plasma were quantified with novel assays. Plasma levels of NDEs were significantly higher in PD (n = 15) than in controls (n = 15) and MSA (n = 15). Plasma levels of ODEs and the ratio of ODE/NDE showed a significant correlation with UPDRS part III scores in MSA-P. This is the first paper that enumerated NDE, ADE, and ODE in human plasma. Plasma levels of NDE and ODE might be a diagnostic and surrogate biomarker for PD and MSA-p, respectively.